Growing food in water - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Home Hydroponic Gardens. P Bradley & C Marulanda. Global Hydroponic Network. 2000. 240 pp.US$ 34.95 E 40.95 Contact GHN for price of mail, or details of distributors in Zimbabwe, Europe, Asia and Latin America GHN PO Box 151 Corvallis, Oregon 9